REDUCE-IT: accumulation of data across prespecified interim analyses to final results. (25th November 2020) - Olshansky, B; Bhatt, D; Miller, M; Steg, P.G; Brinton, E.A; Jacobson, T.A; Ketchum, S.B; Doyle, R.T; Juliano, R.A; Jiao, L; Granowitz, C; Tardif, J.-C; et al.
Abstract: Background: REDUCE-IT (Reduction of Cardiovascular Events with Icosapent Ethyl-Intervention Trial), an event-driven trial, randomized 8, 179 statin-treated patients with elevated triglycerides (TGs) and increased cardiovascular (CV) risk to icosapent ethyl (IPE); pure, stable prescription eicosapentaenoic acid, 4g/day or placebo. 1, 612 primary endpoint events (CV death, nonfatal myocardial infarction [MI], nonfatal stroke, coronary revascularization, or hospitalization for unstable angina) projected 90% power to detect 15% relative risk reduction (5% 2-sided alpha). The key secondary composite endpoint was CV death, nonfatal MI, or nonfatal stroke. An independent data and safety monitoring committee (DMC) performed prespecified interim analyses (IAs) at ∼60% (IA1 31 May 2016 data cutoff; 2.9 y median primary endpoint follow-up) and ∼80% (IA2 01 May 2017; 3.7 y) of events; final analysis included 1, 606 events (06 Sep 2018; 4.9 y median study follow-up). Purpose: Explore REDUCE-IT efficacy and safety across prespecified IAs for insight into progression of robustness and consistency of conclusions. Methods: The interim statistical analysis plan guided study continuation decisions by a prespecified decision-making process, including assessment of safety, treatment arm performance, primary composite endpoint formal analyses, and informal robustness analyses, with no futility or efficacy stopping requirements. Prior to DMC IA study continuation decisions, the need for a mature dataset to support the robustness of final efficacy and safety findings was discussed. Sponsor, Steering Committee, and Clinical Endpoint Committee were blinded throughout. Results: Primary and key secondary endpoints achieved statistical significance at IA1 and IA2 that persisted at final analyses (p-value below final adjusted 2-sided alpha of 0.0437); hazard ratios also remained consistent and similar robustness was observed across individual endpoint components; clarity of findings across endpoints and subgroups improved with more events. Stopping for overwhelming efficacy was discussed at each IA; prior to IA study continuation recommendations, the DMC considered historical examples of failed CV outcome studies for TG-lowering and mixed omega-3 therapies, reflected on the potential for overestimating final demonstrated benefit using incomplete data, and weighed societal impacts of fuller datasets relative to patient therapy access. Conclusions: Consistent, potent efficacy emerged early and persisted across the two prespecified interim and final analyses. The mature dataset demonstrated highly statistically significant reductions in the primary (25%; p=0.00000001) and key secondary (26%; p=0.0000006) endpoints and allowed robust analyses to support overall efficacy and safety conclusions. Allowing the REDUCE-IT dataset to fully mature provided clinicians with robust, consistent, and reliable data upon which to base clinical decisions for IPE in CV risk reduction. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): The study was funded by Amarin Pharma, Inc.